Strategies in mechanical interventions for acute MI: facilitated and rescue PCI - Hellig, Farrel (SA Heart Journal, 2017)
Primary Percutaneous Coronary Intervention (PCI) is the superior strategy for treating acute ST-elevation myocardial infarction (STEMI) as an initial strategy within the first 6 hours from symptom onset. Facilitation of PCI by the use of pre-treatment, prior to planned PCI, with thrombolytic drugs or glycoprotein (GP) IIb/IIIa inhibitors has held theoretical promise for earlier infarct related arterial patency, but has failed to deliver on such promise. Thrombolysis as an initial strategy is inevitable in a large number of STEMI patients due to limited access to primary PCI. This strategy has limited success, and when it fails, rescue PCI has benefit and is recommended. Mechanical methods such as thrombectomy and distal protection, while having an intuitively plausible mechanism for benefit, have also failed to meet expectations and have a limited role in acute STEMI.